Study Of Irrigation Water Quality For Rice Fields In Kayawu Village, North Tomohon District, Tomohon City - Melkison Sanggel; Sofia Wantasen; Adeleyda M. W. Lumingkewas; Frangky J. Paat (Jurnal Agroekoteknologi Terapan, 2023)
This study aims to determine the quality of irrigation water on paddy fields in Kayawu Village, North Tomohon District, Tomohon City. This research was carried out for two (2) months, from September to October 2021. This research was conducted using a survey method, a composite sampling technique. Research samples were taken at two locations, namely the first location upstream and the second location downstream of the rice field irrigation channel in Kayawu Village. Sampling of 3 liters of water at each location, then analyzed at the Laboratory of Research and Industrial Standardization of Manado. The data obtained were analyzed using descriptive statistics. The quality of irrigation water in terms of Parameters: Total Suspended Solid (TSS), the TSS content in the upstream part was 52.2 mg/L and in the downstream part 192 mg/L, still classified as good. Total Dissolved Solid (TDS), TDS levels in the upstream 142 mg/L and in the downstream 241 mg/L, are still relatively good. The levels of Nitrate (NO₃) NO₃ upstream are 6.31 mg/L and downstream are 4 mg/L, still relatively good. The levels of Nitrite (NO₂) NO₂ upstream are 0.00065 mg/L and 0.00065 mg/L in the Downstream, are still relatively good. The levels of Ammonia (NH₃) NH₃ upstream are 0.20 mg/L and in the Downstream are mg/L, are still relatively good. Chloride (Cl), the Cl content in the upstream is 5 mg/L and the downstream is 52 mg/L, is still relatively good. The temperature, at 23.7ºC upstream and 22.5ºC downstream, is still relatively good. The degree of acidity (pH) in the upstream is 7.12 and the downstream is 6.35, which is still relatively good. The results showed that the quality of irrigation water for rice fields in Kayawu Village, North Tomohon District, Tomohon City is still classified as good and meets the requirements as irrigation water in Kayawu, based on Government Regulation No. 22 year 2021. Keywords: Irrigation Water, Irrigation Water Quality, Water Quality Standards Abstrak Penelitian ini bertujuan untuk mengetahui Kualitas air irigasi pada lahan sawah di Kelurahan Kayawu Kecamatan Tomohon Utara, Kota Tomohon. Penelitian ini dilaksanakan selama dua (2) bulan yaitu bulan September sampai bulan Oktober 2021. Penelitian ini dilakukan dengan menggunakan metode survey, teknik pengambilan sampel composite sampling. Sampel penelitian diambil pada dua lokasi yaitu lokasi pertama bagian hulu dan lokasi kedua bagian hilir saluran irigasi areal persawahan di Kelurahan Kayawu. Pengambilan sampel air sebanyak 3 liter ditiap lokasi, kemudian dianalisis di Laboratorium Balai Riset dan Standardisasi Industri Manado. Data yang diperoleh dianalisi menggunakan statistik deskriptif.. Kualitas air irigasi di tinjau dari Parameter :Total Suspended Solid (TSS), kadar TSS pada bagian Hulu 52,2 mg/L dan pada bagian Hilir 192 mg/L, masih tergolong baik. Total Dissolved Solid (TDS), kadar TDS pada bagian Hulu 142 mg/L dan pada bagian Hilir 241 mg/L, masih tergolong baik. Nitrat (NO₃) kadar NO₃ bagian Hulu 6,31 mg/L dan pada bagian Hilir 4 mg/L, masih tergolong baik. Nitrit (NO₂) kadar NO₂ bagian Hulu 0,00065 mg/L dan pada bagian Hilir 0,00065 mg/L, masih tergolong baik. Amonia (NH₃) kadar NH₃ bagian Hulu 0,20 mg/L dan pada bagian Hilir mg/L, masih tergolong baik. Klorida (Cl), kadar Cl pada bagian Hulu 5 mg/L dan pada bagian Hilir 52 mg/L, masih tergolong baik. Suhu, pada bagian Hulu 23,7ºC dan pada bagian Hilir 22,5ºC, masih tergolong baik. Derajat Keasaman (pH) pada bagian Hulu 7,12 dan pada bagian Hilir 6,35, masih tergolong baik. Hasil penelitian menunjukkan bahwa Kualitas Air Irigasi Areal Persawahan Di Kelurahan Kayawu Kecamatan Tomohon Utara Kota Tomohon masih tergolong baik dan memenuhi syarat sebagai Air Iigasi Di Kayawu, berdasarkan Peraturan Pemerintah RI No. 22 tahun 2021. Kata kunci : Air irigasi, Kualitas Air Irigasi, Baku Mutu Air